Role of Geoinformation Expert System in Tasks of Interpretation of Aerospace Information - Ismatova K. R. (Interactive science, 2021)
the article deals with the problem of increasing the efficiency of processing and interpretation of aerospace information. For this purpose, it is proposed to use artificial intelligence methods such as pattern recognition, neural expert systems, geoinformation technologies. Using the example of constructing a geoinformation expert system for assessing the suitability of lands, a method is shown for integrating a set of data and technologies to reduce time and increase the reliability of interpretation of the results of processing satellite information.
Keywords: геоинформационные технологии; нейронные экспертные системы; обработка и интерпретация спутниковой информации; neural expert systems; geoinformation technologies; processing and interpretation of satellite information